QuickTime toolkit - Apple Computer, Inc. (Amsterdam ; Boston : Morgan Kaufmann, 2004)
"When QuickTime application developers get stuck, one of the first places they look for help is example code from Tim Monroe. Finally, Tim's well-crafted examples and clear descriptions are available in book forma must-have for anyone writing applications that import, export, display, or interact with QuickTime movies." Matthew Peterson; University of California, Berkeley; the M.I.N.D. Institute; and author of Interactive QuickTime QuickTime Toolkit Volume One is a programmers introduction to QuickTime, the elegant and potent media engine used by many of Apple's industry-leading services and products (such as the iTunes music store, iMovie, and Final Cut Pro) and also used by a large number of third-party applications. This hands-on guide shows you how to harness the powerful capabilities of QuickTime for your own projects. The articles collected here from the author's highly regarded column in MacTech Magazine are packed with accessible code examples to get you quickly started developing applications that can display and create state-of-the-art digital content. This book begins by showing how to open and display QuickTime movies in a Macintosh or Windows application and progresses step by step to show you how to control movie playback and how to import and transform movies and images. QuickTime Toolkit also shows how to create movies with video data, text, time codes, sprites, and wired (interactive) elements. Part of the official QuickTime Developer Series, publishing the finest books on QuickTime in cooperation with Apple. *Includes a CD-ROM with numerous code examples in C to jumpstart your work *Written in a clear, engaging style by one of Apple's premier media engineers known for his ability to make QuickTime's sophisticated technology accessible to software developers *Offers many undocumented insider tips for making applications that work well in both Mac OS and Windows.
v. 1. Basic movie playback and media types.--v. 2. Advanced movie playback and media types.
Includes indexes.
Keywords: Motion pictures -- Editing -- Data processing; QuickTime; Electronic books